Mesenchymal stem cell-derived exosomes altered neuron cholesterol metabolism via Wnt5a-LRP1 axis and alleviated cognitive impairment in a progressive Parkinson's disease model. (14th September 2022) - Xu, Xiaomin; Li, Zongshan; Zuo, Huirong; Chen, Huimin; Gui, Yaxing
Highlights: Exosomes isolated during dopaminergic neuron differentiation alleviated cognitive impairment in a progressive Parkinson's disease model. Injection of BMSC induced-Exosomes into the striatum altered neuron cholesterol metabolism probably via Wnt5a-LRP1 axis. Injection of BMSC induced-Exosomes into the striatum altered phospholipid composition in hippocampal neurons in PD mice. Abstract: Parkinson's disease (PD) is associated with abnormal metabolism of brain cholesterol, and the metabolites of neuronal cholesterol may also affect neurodegenerative progression. In this study, we aim to explore the therapeutic effect of BMSC derived exosomes on motor and cognitive deficits in α-synuclein (α-Syn) A53T transgenic mice, a progressive PD animal model. Results revealed that rotating rod performance of α-Syn A53T TG mice decreased by 45.4 %±8.6 % at the age of 12 months compared with wide-type (WT) mice. Striatum injection of BMSC quiescent exosomes (BMSC quiescent -EXO) and BMSC induced exosomes (BMSC induced -EXO) rescued the rotation behavior (BMSC quiescent -EXO: 92.3 %±12.5 % P = 0.008; BMSC induced -EXO: 102.3 %±16.7 %, P = 0.006). Although there was no difference in the escape latency within 5 days of Morris water maze learning between groups in the 12-month old mice. The exploration latency was shorter (p < 0.05) in BMSC quiescent -EXO and BMSC induced -EXO groups, the number of explorations and novel object recognition index were significantly increased (p < 0.05). More importantly, the total cholesterol level was increased (p < 0.05), while the content of 24S-hydroxycholesterol significantly decreased (p < 0.05) after intrastriatal injection BMSC quiescent -EXO and BMSC induced -EXO in A53T group. Liquid chromatography-mass spectrometry (LC/MS) was performed to profile phospholipid metabolites in lipid raft of hippocampal neurons, demonstrating that BMSC quiescent -EXO injection caused the decreasing relative percentages of phosphatidylglycerol (PG) and phosphatidylethanolamine (PE) compared to those in A53T mice, while the relative percentages of phosphatidylinositol (PI), phosphatidylserine (PS), and phosphatidylcholine (PC) increased. The cholesterol content of lipid rafts was lower in BMSC quiescent -EXO and BMSC induced -EXO groups than that in A53T group (P < 0.05). In summary, exosomes isolated during BMSC dopaminergic neuron differentiation can significantly improve the motor, learning and memory ability of the progressive PD mice model, and its mechanism may be related to the change of altered phospholipid composition and cholesterol metabolism in hippocampal neurons.